2012
DOI: 10.1155/2012/652683
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Stat1 in the Phagocytosis ofM. avium

Abstract: Mycobacterium aviumis an intracellular pathogen preferentially infecting human macrophages where they activate the JAK/STAT1 pathway. This activation enhances the survival of infected cells, but, at the same time, makes macrophages optimal targets for drugs development against p-tyr701stat1. In this study, we demonstrate that the fast and transient activity of the JAK/STAT1 pathway occurs immediately after macrophages internalization of heat-killed Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Supporting our observation, previous reports suggest that Mycobacteria and its cell wall components, like TDM, downregulate IFNG-mediated responses by inhibiting STAT phosphorylation including p-STAT1. [52][53][54] Of note, individuals with STAT1 deficiency or defects in IFN-JAK-STAT pathway exhibit increased susceptibility to mycobacterial infections. 55,56 Impaired activation of STAT1 or reduced STAT1 phosphorylation in patients with active tuberculosis further underscores our data.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our observation, previous reports suggest that Mycobacteria and its cell wall components, like TDM, downregulate IFNG-mediated responses by inhibiting STAT phosphorylation including p-STAT1. [52][53][54] Of note, individuals with STAT1 deficiency or defects in IFN-JAK-STAT pathway exhibit increased susceptibility to mycobacterial infections. 55,56 Impaired activation of STAT1 or reduced STAT1 phosphorylation in patients with active tuberculosis further underscores our data.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of mycobacteria to induce NO production in murine macrophages through a JAK/STAT-dependent signaling pathway has been previously described 24 25 . However, unlike BCG and MS, known to activate the NF-κB transcriptional factor 22 26 , ML has been shown to be both a weaker stimulator and even an inhibitor of NF-κB activation 22 27 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Various findings suggest that Stat proteins play an important role in bacterial infections [ 5 , 32 ]. In a previous work, we reported that live M. avium infection in macrophages kept the Jak/Stat-1 pathway active for a considerable period (more than 7 days), subsequent to the establishment of an intracellular infection and bacteria replication in the phagosome [ 7 ]. We believe that certain membrane receptors such as FcRs correlated with the Jak/Stat-1 signaling pathway activation and may be able to mediate bacilli phagocytosis or particle internalization in macrophages after opsonization.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study [ 7 ] we showed that internalization of heat-killed M. avium or inert particles induced a fast and transient activity of the Jak/Stat-1 pathway when internalized by Fc γ receptor engagement, probably as a preventive defense mechanism. However, a persistent Stat-1 pathway activation occurs only when an intracellular M. avium infection is established in macrophages.…”
Section: Introductionmentioning
confidence: 99%